2010
DOI: 10.1016/j.neuroscience.2009.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of non-N-methyl-d-aspartic acid glutamatergic transmission in the chick ventral lateral geniculate nucleus

Abstract: Neurotransmission between glutamatergic terminals of retinal ganglion cells and principal neurons of the ventral lateral geniculate nucleus (LGNv) was examined with patch clamp recordings in chick brain slices during electrical stimulation of the optic tract. Since muscarinic and nicotinic receptors are present in high densities in LGNv, the present study examined possible roles of both receptors in modulating retinogeniculate transmission. During whole-cell recordings from LGNv neurons, acetylcholine (ACh, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Retino-GLv terminals are known to be glutamatergic and, as the retino-tectal endings, endowed with nicotinic receptors (Guo et al, 1998(Guo et al, , 2005. Previous physiological work in chick brain slices has shown a nicotinic-dependent presynaptic enhancement of the synaptic transmission between the retinal terminals and the projection cells of the GLv-li (Guo et al, 2005(Guo et al, , 2010. Given their cholinergic character, vine-neurons are the most likely candidates to be the source of such modulation, since as we have shown here they end in the GLv-ne homotopically and in close apposition with the retinal terminals.…”
Section: Synaptic Interactions In the Retino-tecto-glv Networkmentioning
confidence: 99%
“…Retino-GLv terminals are known to be glutamatergic and, as the retino-tectal endings, endowed with nicotinic receptors (Guo et al, 1998(Guo et al, , 2005. Previous physiological work in chick brain slices has shown a nicotinic-dependent presynaptic enhancement of the synaptic transmission between the retinal terminals and the projection cells of the GLv-li (Guo et al, 2005(Guo et al, , 2010. Given their cholinergic character, vine-neurons are the most likely candidates to be the source of such modulation, since as we have shown here they end in the GLv-ne homotopically and in close apposition with the retinal terminals.…”
Section: Synaptic Interactions In the Retino-tecto-glv Networkmentioning
confidence: 99%
“…In addition, retinal terminals in the GLv possess nicotinic receptors (Guo et al, 1998 , 2005 ), which may be modulated by tectal vine-neurons located in layer 10b (Vega-Zuniga et al, 2014 ). Interestingly, it has been shown that cholinergic modulation in the GLv can result in excitatory as well as inhibitory responses through nicotinic and muscarinic receptors (Guo and Chiappinelli, 2002 ; Guo et al, 2010 ). Also, GABAergic synapses are expected to occur due to the GABAergic neurochemical profile of GLv cells (Veenman and Reiner, 1994 ; Vega-Zuniga et al, 2016 ), and the presence of interneurons and projection neurons that have terminals either in the lamina interna (GLv-li) or neuropil (GLv-ne).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established a potent muscarinic modulation of glutamatergic synaptic function at the presynaptic level in the striatum (Higley et al 2009), and in other central nervous regions (Li et al 2002; Guo et al 2010), including the lateral tegmental input onto hypoglossal motoneurons (Bellingham & Berger, 1996). Moreover, a form of EPSC depression induced by muscarinic receptors has been attributed to AMPA receptor internalization in the hippocampus (Volk et al 2007; Dickinson et al 2009).…”
Section: Discussionmentioning
confidence: 99%